Effects of SGLT2 inhibitors on UTIs and genital infections in type 2 diabetes mellitus: a systematic review and meta-analysis - Jiali Liu (Nature Portfolio, 2017)
Abstract Previous trial evidence suggested potential risk of serious urinary tract infections (UTIs) and genital infections in type 2 diabetes patients using sodium glucose co-transporter-2 inhibitors (SGLT2) inhibitors. We conducted a systematic review and meta-analysis to assess the effects of SGLT2 inhibitors on UTIs and genital infections in patients with type 2 diabetes. In total, 77 RCTs involving 50,820 participants were eligible. The meta-analyses of randomized controlled trials (RCTs) showed no significant difference in UTIs between SGLT2 inhibitors versus control (2,526/29,086 vs. 1,278/14,940; risk ratio (RR) 1.05, 95% confidence interval (CI) 0.98 to 1.12; moderate quality evidence), but suggested increased risk of genital infections with SGLT2 inhibitors (1,521/24,017 vs. 216/12,552; RR 3.30, 95% CI 2.74 to 3.99; moderate quality evidence). Subgroup analyses by length of follow up (interaction p = 0.005), type of control (interaction p = 0.04) and individual SGLT2 inhibitors (interaction p = 0.03) also showed statistically significant differences in genital infections. The upcoming major trials may provide important additional insights on UTIs, and more efforts are needed to address comparative effects of each individual SGLT2 inhibitors on the infections.